2006
DOI: 10.1002/hc.20198
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel thiazole and pyrrolothiadiazine derivatives from aldehyde thiosemicarbazones

Abstract: Substituted thiosemicarbazones 7a-e reacted with ethenetetracarbonitrile (TCNE) in ethyl acetate with formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…19 5-Amino-3-(substituted benzylidenamino)-2-phenylimino-2,3-dihydrothiazole-4-carbonitrile is one of the products which have been isolated from the reaction of aldehyde thiosemicarbazones with tetracyanoethylene (TCNE). 20 Mesoionic 1,2,4-triazolium-3-thiolate derivatives were synthesized from the reaction of Nsubstituted 2-phenylhydrazinecarbothioamides with TCNE. 21 Herein, we report our investigation on the reaction of 2-substituted hydrazinecarbothioamides 1a-e with TCNE 2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…19 5-Amino-3-(substituted benzylidenamino)-2-phenylimino-2,3-dihydrothiazole-4-carbonitrile is one of the products which have been isolated from the reaction of aldehyde thiosemicarbazones with tetracyanoethylene (TCNE). 20 Mesoionic 1,2,4-triazolium-3-thiolate derivatives were synthesized from the reaction of Nsubstituted 2-phenylhydrazinecarbothioamides with TCNE. 21 Herein, we report our investigation on the reaction of 2-substituted hydrazinecarbothioamides 1a-e with TCNE 2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that substituted thiosemicarbazones 1a , 1b , 1c , 1d , 1e reacted with TCNE ( 2 ) in ethyl acetate with the formation of products 3 to 5 (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…Also, according to the formation of 3 , 4 , 5 , both the thioxosulfur and azomethine groups had taken part in heterocyclization .…”
Section: Introductionmentioning
confidence: 99%
“…A novel and a efficient procedure for the synthesis of thiosemicarbazones has been achieved via a multicomponents and catalyst‐free reaction of phenyl or p ‐ chlorophenyl isothiocyanate, hydrazine, and aldehydes or ketones [33]. Besides, thiosemicarbazones are versatile building blocks in the synthesis of densely substituted heterocycles [34–40]. It has been reported earlier that, isatin‐3‐thiosemicarbazones were cyclized to 5 H ‐ as ‐triazino[5,6‐ b ]indole‐3‐thiones in aqueous K 2 CO 3 [41–43].…”
Section: Introductionmentioning
confidence: 99%